A systematic literature review of gray level co-occurence matrix on plants - Anwar Sadad; Ema Utami; , Anggit Dwi Hartanto (Institute of Computer Science (IOCS), 2023)
The Gray Level Co-Occurrence Matrix method includes contrast, correlation, energy and homogeneity then is processed using an artificial neural network method for its classification. This literature tries to learn about the process of the GLCM method. This is done to understand the methods that researchers use to collect data from various sources, process the data that has been collected, and classify the data so that it becomes information that is easier to understand. researchers collect, screen, and review the research found using a Systematic Literature Review approach. Researchers pooled research from ScienceDirect, Google Scholar, and Elsevier by selecting studies published from 2020 to 2023. The purpose of the researchers conducting this literature review was to understand the GLCM method in parks, gain an understanding of data collection techniques, methods, and study the results of the research. previously. This study collects and summarizes 12 studies. The study was conducted regarding the method of data collection, the methods used, and the results of the research.